The Influence of Perceived Nostalgia and Perceived Value on Post Purchase Intention Through Brand Trust on Levi's Products as a Mediating Variable (Study on Levi's Gen Z Product Users on the TikTok Platform @Levisstoreid) - Putri, Istifani Salsabila; Fazizah, Amma (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of Perceived Nostalgia and Perceived Value on Post Purchase Intention, with Brand Trust as a mediating variable, on Gen Z consumers who use Levi's products on the Tiktok platform. The phenomenon of increasing emotional attachment of young consumers to products with historical value and past experiences encourages the importance of understanding emotional value-based marketing strategies. Using a quantitative approach and path analysis through SPSS software, this study involved 95 active respondents who fit the demographic criteria. The results showed that Perceived Nostalgia and Perceived Value had a significant effect on Brand Trust, and directly increased Post Purchase Intention. However, Brand Trust did not show a significant effect on Post Purchase Intention, indicating that repurchase intention was more influenced by emotional experience and perceived value than brand trust itself. These findings provide strategic implications for marketers in building a more personal, emotional, and relevant approach to young consumers through adaptive and nostalgia-based digital campaigns. This study also enriches the marketing literature by highlighting the dynamics of Gen Z behavior in the context of heritage products and social media use.